Christian Teachers in Second-Century Rome : Schools and Students in the Ancient City - H. Snyder, Gregory (Vigiliae Christianae, Supplements Ser, 2020)
Intro -- ‎Contents -- ‎Figures -- ‎Notes on Contributors -- ‎Introduction -- ‎Chapter 1. Jewish Teachers in Rome? (Lieu) -- ‎Chapter 2. Were There Valentinian Schools? (Thomassen) -- ‎Chapter 3. Esoteric Knowledge in Platonism and in Christian Gnosis (Markschies) -- ‎Chapter 4. Visual Representations of Early Christian Teachers and of Christ as the True Philosopher (Jensen) -- ‎Chapter 5. Christians as and among Writer-Intellectuals in Second-Century Rome (Wendt) -- ‎Chapter 6. Problems of Profiling Marcion (Löhr) -- ‎Chapter 7. Justin Martyr as an Organic Christian Intellectual in Rome (Rivas Rebaque) -- ‎Chapter 8. Tatian Theodidaktos on Mimetic Knowledge (Herrero de Jáuregui) -- ‎Chapter 9. Shoemakers and Syllogisms: Theodotus "the Cobbler" and His School (Snyder) -- ‎Author Index -- ‎Source Index.